Impact of credit and collection management on the liquidity of the company AFA GROUP, Trujillo 2022. (LACCEI, 2024)
The main objective of this study was to determine how credit and collection management affects the liquidity of the company AFA GROUP of Trujillo in the year 2022. This is a mixed-applied, non-experimental, longitudinal and descriptive-explanatory study, which includes as study population the company AFA GROUP and evaluates three periods: 2019, 2020 and 2021. Interviews and documentary analysis were used for data collection. The results indicate that inefficient credit and collection management has a negative impact on the liquidity of the company AFA GROUP, reducing its liquidity ratios by 77% in 2021. In that year, the company had particular difficulties in meeting its short-term debts, with an acid test ratio of 0.39 and a cash ratio of 0.03. In conclusion, it was determined that poor accounts receivable management can generate liquidity problems and make it difficult to meet obligations to third parties.